Meningkatkan Potensi Ekonomi Islam di Komplek Makam Sunan Gunung Jati - Rofingatun Nguluwiyah; Gumilar Irfanullah; Umayyah Umayyah; Iksan Ghofur; Indra Gunawan (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the increase in Islamic economic potential in the Sunan Gunung Jati tomb complex. this research uses a qualitative approach with descriptive-analytical method. The results and discussion in this study show that, economic potential can be characterized by the success of an increase in income in the community's economy. As well as, increasing the tourism sector, and sales in Indonesia are able to make the country's economy and society increase every year. Thus, one of the areas that has increased its economy is the Sunan Gunung Jati tomb complex, whose residents choose to improve their economy in the field of religious tourism sector and the sale of food, drinks and clothing with batik motifs and pictures of walingsanga. The limitation in the research is in terms of data collection which only uses previous literature, so it is recommended for further research, to collect data directly into the field.